Un journal « mal conçu et mal rédigé » : le Corriere d’Italia (1807-1808), ou comment relire les pratiques politiques des exilés italiens dans le Paris napoléonien - Paolo Conte (Laboratoire Italien)
On 15 August 1807, in Paris a new newspaper appears, whose title is the Corriere d’Italia. Drafted in Italian, it would be published every day until the spring by the French printer Guitard. Thanks to its editorial-line, this newspaper wins the Emperor’s support, who is always interested in controlling the dissemination of news beyond the Alps. In fact, despite the opposition of the Viceroy of the Kingdom of Italy Eugène de Beauharnais and the Minister of Foreign Affairs Ferdinando Marescalchi, Napoleon decrees a government funding to allow facilitate its diffusion in Italy. After examination of the distribution of the Corriere, this paper deepens its editorial line in order to understand the political purposes supporting this initiative. In this way, the aim is to reduce the dichotomy between political practices and cultural practices: the latter is not a simple alternative to the first one, but a way of re-articulating, in another context and under other forms, the commitment of previous years.